Quantifying the Interoperability of Open Government Datasets. - Colpaert, Pieter; Van Compernolle, Mathias; De Vocht, Laurens; Dimou, Anastasia; Sande, Miel Vander; Verborgh, Ruben; Mechant, Peter; Mannens, Erik (Computer (00189162), 2014)
A proposed technique quantifies the semantic interoperability of open government datasets with three metrics calculated using a set of statements that indicate for each pair of identifiers in the system whether or not they represent the same concept.